Value of Ultrasonography in Detection of Diaphragmatic Injuries Following Thoracoabdominal Penetrating Trauma; a Diagnostic Accuracy Study - Sharifi, Ali (Arch Acad Emerg Med, 2019)
INTRODUCTION: Diagnosis of diaphragmatic rupture following thoracoabdominal penetrating trauma is very challenging in asymptomatic patients with stable vital signs. This study aimed to evaluate the diagnostic accuracy of focused assessment with sonography for trauma (FAST) in this regard. METHODS: This cross-sectional study was performed on patients referring to emergency department due to left thoracoabdominal stab wound during 2 years. All patients initially underwent ultrasonography and the screening performance characteristics of FAST in detection of diaphragmatic injuries were calculated, considering the findings of diagnostic laparoscopy as the gold standard test. RESULTS: Twenty-four patients with the mean age of 33 ± 10.64 years (16-61 years) were studied (100% male). The mean chest wall laceration size was 2.7 ± 2.7 cm (1-10 cm) and the most frequent location of wounds was posterior chest wall (42%) and in the 6(th) and 7(th )intercostal space (50%). Diaphragmatic rupture was seen in 4 (16.7%) patients based on diagnostic laparoscopy. Sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratio of FAST in detection of diaphragmatic raptures were 50% (95% CI: 9.18 – 90.8), 100% (95% CI: 79.9 – 100.0), 100% (95% CI: 19.8 – 100.0), 9.1% (95% CI: 1.5 – 30.6), Infinity, and 0.1 (95% CI: 0.02 – 0.37), respectively. The overall accuracy of FAST in this regard was 75.0% (95% CI: 42.3 – 100.0). CONCLUSION: In patients with penetrating trauma to the left thoracoabdominal region, FAST cannot be the definitive alternative to diagnostic laparoscopy to detect diaphragm rupture.